Exhaled breath analysis in childhood rheumatic disorders—a longitudinal study. (19th April 2016) - Hendel, N; Akmatov, M K; Hamel, J; Vogelberg, C; Pessler, F
Abstract: We aimed to evaluate the fraction of exhaled nitric oxide (FE NO50 ) and deaerated exhaled breath condensate pH (dEBCpH) as non-invasive markers of subclinical airway inflammation in pediatric patients with rheumatologic disorders. We determined FE NO50 and dEBCpH in a prospective study spanning at least 12 months, comprising 85 pediatric patients with rheumatologic disorders, including juvenile idiopathic arthritis (JIA, n   =  63), chronic recurrent multifocal osteomyelitis (CRMO, n   =  6), systemic lupus erythematosus (SLE, n   =  3), juvenile dermatomyositis (JDM, n   =  1) and other rheumatic disorders ( n   =  12). dEBCpH was determined once in a group of children without evidence of rheumatologic or pulmonary disease (controls, n   =  90). Findings were correlated with results of pulmonary function tests. Atopic sensitization was assessed by RAST or skin prick test in 76 patients. Atopic sensitization was detected in 34% (26/76) of patients. Neither FE NO50 nor dEBCpH correlated with disease activity, but intermediately (20–35 ppb) or highly elevated (>35 ppb) levels were observed at least once in 26 patients (31%), 19 of whom had atopic sensitization. Median dEBCpH did not differ between cases and controls (8.05 versus 8.02; p   =  0.48). Median dEBCpH decreased slightly over the study period ( p   =  0.02), whereas FE NO50 values did not change significantly ( p   =  0.89). There were several patients with significantly abnormal dEBCpH values that could not be readily explained by diagnosis, higher disease activity, medications, or atopic sensitization. Thus, there were no consistent abnormalities in FE NO50 or dEBCpH in this cohort of Caucasian patients with relatively stable rheumatologic disorders, but there were some patients with abnormal values of unknown significance.